STUDY ON THE OBSTACLES OF 2ND SEMESTER STUDENTS IN ASKING QUESTIONS DURING THE LEARNING PROCESS - Noval Hestalda Noval (CV Grasta Glory, 2025)
This study aims to find out the obstacles 2nd-semester college students face in asking questions during the learning process. This study uses a descriptive qualitative approach. The subject of the study is a second-semester student of Elementary School Teacher Education at PGRI Silampari University. The data collection technique uses questionnaires and observation methods. Data analysis was carried out using the Miles and Huberman models, which consisted of data reduction, data presentation, and conclusions. The results of this study show that the main obstacles come from personal barriers, such as shyness, lack of confidence, fear of negative judgement, and difficulty in formulating questions. On the other hand, social barriers such as peer influence and a less supportive classroom environment have not proven to be major . Academic barriers also contribute, especially related to a lack of understanding of the material. On the other hand, obstacles from lecturers are considered not to be found in this study. Many college students argue that lecturers are sufficiently transparent, provide space for discussion, and are quick in answering questions asked by college students. This study concludes that college students' courage to ask questions is greatly influenced by mental readiness, active study habits, and critical thinking skills that need to be continuously developed through learning methods that support participation, confidence, and courage to ask questions.